2019
DOI: 10.1186/s12889-019-7431-8
|View full text |Cite
|
Sign up to set email alerts
|

Levels of outpatient prescribing for four major antibiotic classes and rates of septicemia hospitalization in adults in different US states - a statistical analysis

Abstract: Background Rates of sepsis/septicemia hospitalization in the US have risen significantly during recent years. Antibiotic resistance and use may contribute to those rates through various mechanisms, including lack of clearance of resistant infections following antibiotic treatment, with some of those infections subsequently devolving into sepsis. At the same time, there is limited information on the effect of prescribing of certain antibiotics vs. others on the rates of septicemia and sepsis-relate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…The high number of AB prescriptions has largely contributed to medical concerns about ABresistance. A study done in the USA investigated penicillin and fluoroquinolone, and the findings suggested a directly proportionate relationship between AB prescription and AB resistance [4]. Society members, physicians, and laypersons should have sufficient knowledge and awareness regarding AB resistance to contain and slow its evolution.…”
Section: Introductionmentioning
confidence: 99%
“…The high number of AB prescriptions has largely contributed to medical concerns about ABresistance. A study done in the USA investigated penicillin and fluoroquinolone, and the findings suggested a directly proportionate relationship between AB prescription and AB resistance [4]. Society members, physicians, and laypersons should have sufficient knowledge and awareness regarding AB resistance to contain and slow its evolution.…”
Section: Introductionmentioning
confidence: 99%